Greater Consideration of Animals Will Enhance Coastal Restoration Outcomes. (12th October 2022) - Sievers, Michael; Brown, Christopher J; Buelow, Christina A; Hale, Robin; Ostrowski, Andria; Saunders, Megan I; Silliman, Brian R; Swearer, Stephen E; Turschwell, Mischa P; Valdez, Stephanie R; Connolly, Rod M
Abstract: As efforts to restore coastal habitats accelerate, it is critical that investments are targeted to most effectively mitigate and reverse habitat loss and its impacts on biodiversity. One likely but largely overlooked impediment to effective restoration of habitat-forming organisms is failing to explicitly consider non-habitat-forming animals in restoration planning, implementation, and monitoring. These animals can greatly enhance or degrade ecosystem function, persistence, and resilience. Bivalves, for instance, can reduce sulfide stress in seagrass habitats and increase drought tolerance of saltmarsh vegetation, whereas megaherbivores can detrimentally overgraze seagrass or improve seagrass seed germination, depending on the context. Therefore, understanding when, why, and how to directly manipulate or support animals can enhance coastal restoration outcomes. In support of this expanded restoration approach, we provide a conceptual framework, incorporating lessons from structured decision-making, and describe potential actions that could lead to better restoration outcomes using case studies to illustrate practical approaches.